The grouping system and local distribution pattern analysis of Javan green peafowl (Pavo muticus muticus, Linnaeus 1758) population in Baluran and Alas Purwo National Parks, East Java, Indonesia - JARWADI BUDI HERNOWO; HADI SUKADI ALIKODRA (Society for Indonesian Biodiversity, 2018)
Hernowo JB, Alikodra HS. 2018. The grouping system and local distribution pattern analysis of Javan green peafowl (Pavo muticus muticus, Linnaeus 1758) population in Baluran and Alas Purwo National Parks, East Java, Indonesia. Biodiversitas 19: 1690-1695. The Javan green peafowl population lives in a group system. The population applies a small size group system. The distribution of the birds in Java Island is randomly fragmented and isolated in several types of habitat and each has a small number of individuals in every group. Baluran and Alas Purwo National Parks, East Java, Indonesia as part of Javan green peafowl (Pavo muticus muticus, Linnaeus 1758) distributions have been selected for the study on the grouping system and the analysis of local distribution. The research was aimed at obtaining data and information on the grouping system and local distribution of Javan green peafowl population in Baluran and Alas Purwo National Park. The number of individuals and groups was counted by applying a transect method and a concentration method on every type of habitat where peafowls are present. The distribution pattern data were analyzed by using a formula (Ludwig and Reynolds 1988). The results indicate that Javan green peafowl population is living in small groups (2-4 birds). There are 5 types of Javan green peafowl groups in Baluran National Park (BNP) and Alas Purwo National Park (APNP). The dominant group is adult female group consisting 3 individual members. The leader of the group is a female bird. Adult males live in solitary. The group system among Javan green peafowl populations is a strategy of the birds. Local distribution of Javan green peafowl populations in Baluran and Alas Purwo National Parks is mostly in the form of clumped dispersion.